2004
DOI: 10.1128/jb.186.21.7450-7455.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stability ofbmr3mRNA Results in a Multidrug-Resistant Phenotype inBacillus subtilis

Abstract: A spontaneous mutant isolated in the presence of a high concentration of puromycin acquired a multidrugresistant phenotype. Expression of the bmr3 gene was dramatically increased. A base substitution, T to A at the ؉4 position, detected in the mutant resulted in the stabilization of bmr3 mRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…5A. The moderately structured and strongly structured sequences were patterned, respectively, after the wild-type and mutant forms of mdr (or bmr3) mRNA (29). The strongly structured sequence was shown to increase mdr mRNA stability at least fourfold.…”
Section: Resultsmentioning
confidence: 94%
“…5A. The moderately structured and strongly structured sequences were patterned, respectively, after the wild-type and mutant forms of mdr (or bmr3) mRNA (29). The strongly structured sequence was shown to increase mdr mRNA stability at least fourfold.…”
Section: Resultsmentioning
confidence: 94%
“…trp Leader RNA with a 5Ј Stabilizer-Experiments in our laboratory and others (31)(32)(33), as well as a survey of stable B. subtilis mRNAs (20), have indicated that a 5Ј-terminal stem loop structure should have a strong stabilizing effect. We predicted that addition of such a structure would stabilize greatly the extremely unstable D1 RNA.…”
Section: Rna Sequencementioning
confidence: 99%
“…(B) Sequence and predicted structure of the 5ЈSS mRNA stabilizer. on April 30, 2019 by guest http://jb.asm.org/ mol) and has been shown in other contexts to function as a 5Ј stabilizer (13,18). The addition of the 5ЈSS to ⌬ermC mRNA substantially increased the half-life in the wild-type strain to 18.3 min ( Table 1).…”
mentioning
confidence: 82%